A Study of Compost as an Adsorbent for Congo Red Dye Removal Process - Gabriel Andari Kristanto; Ariessyawtra Raindra Lamurvie; William Koven (Reaktor, 2017)
The human population continues to grow annually, and so does the number of textile industries. In textile industry, synthetic dye is one of the most polluting substance in its wastewate which the conventional treatment processes are usually ineffective. Another option is using activated carbon to remove the dye, but carbon is an expensive material. It is is interesting that  material that is rich in carbon, such as compost, may become an alternative solution. The objective of the present study was to assess the capability of compost in treating wastewater dye by determining the optimum compost dosage, particle size, and column height, while considering dye percentage removal and adsoprtion capacity. The optimum compost dosage was 8g/L and the optimum particle size was 1–2 mm in treating the 200 ppm Congo Red dye molecule, resulting in 20.49% removal and a 5.33 mg/g adsorption capacity. The optimum compost column height was 60 cm with 90% removal, and the adsorption capacity was 0.38 mg/g. The dye molecule wore off tthe compost, therefore fresh compost must be introduced in order to maintain its percentage removal level. The compatibility of isotherm model developed in this study with the Freundlich model is similar with previous studies.    Keywords: compost; congo red dye;adsorbent, batch, column